Children are children are children : an activity approach to exploring Brazil, France, Iran, Japan, Nigeria and the U.S.S.R. - Cole, Ann; Axeman, Lois (Little, Brown, 1978)
Describes the life and customs of Brazil, Nigeria, Japan, Iran, France, and the Soviet Union with suggestions for related activities and projects.